1985
DOI: 10.1139/m85-218
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial control of Agromyces ramosus in soil

Abstract: Agromyces ramosus occurs in high numbers in many soils. It also is a known predator of various gram-positive and gram-negative soil bacteria, including Azotobacter vinelandii. Based on this, it would seem that, in natural soil, A. ramosus should control the population sizes of these soil bacteria. As a partial test of this assumption, we examined the possibility that soil might contain other bacterial predators that could hold A. ramosus in check. Three gram-negative bacterial predators of A. ramosus were isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…In conformity with Rules 15, 17, 23a and 37a (1) Cupriavidus necator was described by Makkar & Casida (1987) to accommodate a non-obligate bacterial predator of various Gram-negative and Gram-positive soil bacteria and fungi (Byrd et al, 1985;Sillman & Casida, 1986;Zeph & Casida, 1986). The single known isolate, strain N-1 T (=LMG 8453 T ), was obtained from soil in the vicinity of University Park, PA, USA.…”
mentioning
confidence: 96%
“…In conformity with Rules 15, 17, 23a and 37a (1) Cupriavidus necator was described by Makkar & Casida (1987) to accommodate a non-obligate bacterial predator of various Gram-negative and Gram-positive soil bacteria and fungi (Byrd et al, 1985;Sillman & Casida, 1986;Zeph & Casida, 1986). The single known isolate, strain N-1 T (=LMG 8453 T ), was obtained from soil in the vicinity of University Park, PA, USA.…”
mentioning
confidence: 96%
“…The cells decrease somewhat in size and become more rounded as cultures age, or when the organism is placed in contact with soil during soil column studies (Byrd et al, 1985). In soil, the rounded forms of C. necator appear to be dormant (Byrd et al, 1985). C. necator reproduces by binary fission and is motile by 2-10 peritrichous flagella.…”
mentioning
confidence: 99%
“…C. necator produces the heat-labile, magnesium-related growth initiation factor (GIF) that was first described by Casida (1984) and that is produced by various types of bacteria in soils. This GIF can initiate the growth of Agromyces ramosus and other species in soil (Casida, 1984;Byrd et al, 1985), thereby increasing the supply of suitable prey cells for nonobligate bacterial predators like C. necator. The actual mechanism by which C. necator kills its prey cells is not yet known, although Casida (1987) has suggested that a copper-related peptide used to scavenge copper from the environment (see below) might also be used to deliver excess (and toxic) amounts of copper to prey cells.…”
mentioning
confidence: 99%
See 2 more Smart Citations